Konsep Reconnecting With Nature pada Desain Hospitality Banyan Tree Escape - Primadewi , Siluh Putu Natha; Idedhyana, Ida Bagus; Rijasa, Made Mariada (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2024)
Banyan Tree Escape is located in Payangan Gianyar Bali and has a unique design concept